The Influence of Leadership Style, Work Environment, and Compensation on Teacher Performance - Julham Efendi; Ade Parlaungan Nasution; Aziddin Harahap (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Teacher performance plays a very important role in the advancement of education in Indonesia, if the teacher’s performance is bad, then it will not lead to the best learning outcomes. All instructors must be able to complete their tasks quickly and accurately both in management and teaching. High-class sizes, a lack of student focus and dedication, and an abundance of extracurricular activities mean that teachers’ attention is not only divided but also thinly spread. While rare, teacher absences and free time during courses can hinder learning. In addition, the early departure of teachers is a very demoralizing event, and there are positive aspects such as the principal’s management style, unpleasant working atmosphere, and unclear salary. Teacher effectiveness plays an important role in supporting education in Indonesia. The program objectives will also not be achieved optimally if the teacher's performance is below standard. This study aims to analyze the influence of the principal’s leadership style, work environment, and compensation on teacher performance. The type of research used is quantitative research. The results of this study conclude that the principal’s leadership affects teacher performance, the work environment influences teacher performance, and compensation also affects teacher performance.